Pengembangan Instrumen Penilaian Sikap Disiplin Menggunakan Skala Likert dalam Pembelajaran Tematik Kelas IV SD - Fransiska Ayuka Putri Pradana; Mawardi Mawardi (FONDATIA, 2021)
The current problem faced regarding environmental condition is the low public awareness to protect and preserve the environment. It is because of the lack of society’s discipline in protecting the environment, so it needs something to track their discipline attitude to take care of the environment. Here I focus on the students' discipline attitude as an object of my research. Thus, this research aimed to produce a discipline attitude assessment instrument using Likert scale and to find out the validity and feasibility of the discipline attitude assessment instrument using Likert scale for thematic learning in fourth grade students of elementary school about environmental discipline. This research implemented research and development (R&D) design. The instrument validity was analyzed by an attitude assessment expert with a score of 85.7%, by an instructional design expert with a score of 91.8%, and by a linguist with a score of 91.3%. Based on the validations of those three aspects, the score was categorized as ‘very high’. Therefore, the developed discipline attitude assessment instrument using Likert scale is very feasible to use.